Label-free imaging and identification of typical cells of acute myeloid leukaemia and myelodysplastic syndrome by Raman microspectroscopy1. Issue 4 (21st February 2015) - Vanna, R.; Ronchi, P.; Lenferink, A. T. M.; Tresoldi, C.; Morasso, C.; Mehn, D.; Bedoni, M.; Picciolini, S.; Terstappen, L. W. M. M.; Ciceri, F.; Otto, C.; Gramatica, F.
<x xml:space="preserve">Abstract</x> Heamatopoietic cancer cells from patients were objectively and accurately recognized by high-resolution Raman imaging and their characteristic Raman spectra.